Impact of rapid maxillary expansion on nasomaxillary complex volume in mouth-breathers - Mario Cappellette Jr; Fabio Eduardo Maiello Monteiro Alves; Lucia Hatsue Yamamoto Nagai; Reginaldo Raimundo Fujita; Shirley Shizue Nagata Pignatari
ABSTRACT Objective: To assess the volumetric changes that occur in the nasomaxillary complex of mouth-breathing patients with transverse maxillary deficiency subjected to rapid maxillary expansion (RME). Methods: This was a controlled, prospective intervention study involving 38 mouth-breathing patients presenting with transverse maxillary deficiency, regardless of malocclusion type or race. Twenty-three of them comprised the experimental group, which was composed of 11 (47.8%) boys, and 12 (52.2%) girls, with a mean age of 9.6 years, ranging from 6.4 to 14.2 years and standard deviation of 2.3 years; and 15 of them comprised the control group, composed of 9 (60%) boys and 6 (40%) girls with an mean age of 10.5 years, ranging from 8.0 to 13.6 years, and standard deviation of 1.9 years. All patients were scanned (CT) according to a standard protocol: Initial CT (T1), and CT three months thereafter (T2), and the patients in the experimental group were treated with RME using a Hyrax expander for the correction of maxillary deficiency during the T1-T2 interval. The CT scans were manipulated using Dolphin® Imaging version 11.7 software for total and partial volumetric assessment of the nasomaxillary complex. Results: The results revealed that in the experimental group there was a significant increase in the size of the structures of interest compared to the control group, both in general aspect and in specific regions. Conclusions: Rapid maxillary expansion (RME) provided a significant expansion in all the structures of the nasomaxillary complex (nasal cavity, oropharynx, right and left maxillary sinuses).